Giardia duodenalis in sympatric wild reindeer and domestic sheep in Norway - Kjersti Selstad Utaaker; Tsegabirhan Kifleyohannes; Bjørnar Ytrehus; Per-Anders Robertsen; Olav Strand; Lucy J. Robertson (International Journal for Parasitology: Parasites and Wildlife)
Wild and semi-domesticated reindeer graze freely on natural pastures in Norway, often sharing these with domestic sheep and other domestic and wild ruminants. In this study, faecal samples from wild reindeer and domestic sheep were collected from two areas in southern Norway and analysed to assess the occurrence and assemblage of Giardia duodenalis. Among 162 wild reindeer samples, 25 (15%) were positive for Giardia, showing high infection intensities, with most of the samples belonging to sub-assemblage AI, which has zoonotic potential. Interestingly, this study did not detect subassemblage AIII, known to be found in wild ruminants. Among 45 sheep samples, 13 (29%) were Giardia-positive, with most belonging to assemblage E.The finding of predominantly assemblage AI in the reindeer was surprising, particularly given the large proportion of sheep shedding assemblage E Giardia cysts. As the number of sheep on these natural pastures far outnumbers the wild reindeer, it is intriguing that they do not seem to share Giardia assemblages.